The Influence Of Leadership On Employee Performance (Study On Perumda Bpr Garut) - Rusdian, Suca; Diandra, Patiah Nur (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This research is based on the tendency for employee performance at Perumda BPR Garut to decline. This phenomenon can be caused by various factors, one of which is a low level of leadership. The purpose of this research is to find out how leadership is at Perumda BPR Garut, how employees are performing at Perumda BPR Garut, how leadership influences employee performance at Perumda BPR Garut. This research uses a quantitative research approach with survey research methods and descriptive and associative types of explanation. The population of this study was some of the employees of Perumda BPR Garut, totaling 63 people. The sampling technique uses probability sampling technique with non-saturated sampling type. The data analysis technique used in formulating research problems is rating scale analysis, correlation coefficient analysis, coefficient of determination test and hypothesis testing. From the results of descriptive statistical analysis, a rating scale value was obtained of 1,854 for the leadership variable and 4,125 for the performance variable. These results show that all research variables are in the very good category but not yet optimal. Based on the results of the correlation test, it is clear that leadership has a moderate influence on employee performance with an r value of 0.725, with a coefficient of determination of 52% and the remaining 48% is influenced by other factors not studied such as job satisfaction, work motivation, stress levels and others. and so on... Hypothesis test results show that leadership has a positive and significant effect on employee performance with a calculated t value of (8,209) t table (1,670) and a significance value of 0.000 0.05.